A rare case of static bone cavity in the anterior mandibular region of a 10-year-old boy. (June 2021) - Watanabe, Akira; Yoshida, Shuji; Kato, Hiroshi; Matsuzaka, Kenichi; Takano, Masayuki
Abstract: Introduction: Static bone cavity (SBC) is a bone defect that develops as a result of localized pressure from tissues surrounding the mandible. It is most commonly observed in the mandibular angle of adult males caused by the submandibular gland. The condition is asymptomatic and requires no treatment. The frequency of onset is rare, especially in the anterior mandible, and SBC is extremely difficult to diagnose in children. Presentation of case: This report is on a case of SBC in the anterior mandible of a 10-year-old boy. The condition could not be diagnosed after panoramic radiograph and Magnetic Resonance Imaging (MRI) analyses. Computed-topography (CT) imagery revealed an oval-shaped depression 6 × 5 × 3 mm in size at the lingual apex of the mandibular left lateral tooth. Diagnosing the patient was difficult and a tumor was suspected. For treatment, the tumor-like lesion was resected and the fistula in the periosteum was sutured and closed. One year later, the defect on the lingual mandibular bone had ossified and recovered. Conclusion: The incidence of SBC in children is rare and the condition is difficult to diagnose because of the small size of the lesions, however in this study, CT imagery proved to be useful. SBC was detected in the subject in early childhood, and his postoperative course suggested that the lesion developed as a result of glandular tissues herniating through the periosteum and causing compression on the mandible, which resulted in bone resorption. In other words, herniation of normal salivary glandular tissues were a cause of SBC. Highlights: Children's SBC is seldomly observed in the anterior tooth region. Lesions that develop in such rare locations make differential diagnoses difficult. This case showed the initial stages of SBC. The herniated normal salivary glands was determined as a likely cause of SBC.